Mosquito transmission of the rodent malaria parasite Plasmodium chabaudi - Spence Philip J; Jarra William; Lévy Prisca; Nahrendorf Wiebke; Langhorne Jean (Malaria Journal, 2012)
Abstract Background Serial blood passage of Plasmodium increases virulence, whilst mosquito transmission inherently regulates parasite virulence within the mammalian host. It is, therefore, imperative that all aspects of experimental malaria research are studied in the context of the complete Plasmodium life cycle. Methods Plasmodium chabaudi chabaudi displays many characteristics associated with human Plasmodium infection of natural mosquito vectors and the mammalian host, and thus provides a unique opportunity to study the pathogenesis of malaria in a single infection setting. An optimized protocol that permits efficient and reproducible vector transmission of P. c. chabaudi via Anopheles stephensi was developed. Results and conclusions This protocol was utilized for mosquito transmission of genetically distinct P. c. chabaudi isolates, highlighting differential parasite virulence within the mosquito vector and the spectrum of host susceptibility to infection initiated via the natural route, mosquito bite. An apposite experimental system in which to delineate the pathogenesis of malaria is described in detail.